Health literacy and health related behaviour in the hospital workforce - Sattler, Rico (2019)
According to surveys, health literacy amongst the Austrian population is with more than 50% insufficient scores, problematic. There has to the knowledge of the author of this thesis not been a study measuring the health literacy levels amongst hospital employees (Sattler & Muschnig, 2019). Lifestyle choices have a strong influence on the health of individuals and groups. The connection between health literacy and health related behaviour is not yet fully understood. This study was designed as a joint thesis with the aim to explore the relationship between health literacy and health related behaviour. The first part, using online questionnaires consisting of the European Health Literacy Survey (HLS-EU-Q47) and the Newest Vital Sign (NVS), was designed to evaluate health literacy levels amongst the hospital workforce, the second part consisted of semi-structured interviews, aimed to explore health related behaviour in relation to health literacy amongst the hospital workforce. This thesis presents the lifestyle related part of the study. No direct correlation between health literacy and healthy lifestyle choices could be found. Definition of health literacy varied amongst participants. The awareness of HL was not related to making healthy lifestyle choices. Key moments that functioned as wake-up calls, and general motivation to live healthy were defined as leading factors for lifestyle changes towards healthier behaviours.